Long-life afterglow polymer material as well as preparation method and application thereof

By using aromatic polyester and tris(4-borate phenyl)amine in the long afterglow polymer material to form an electron donor/acceptor excitation composite, the problem of insufficient long afterglow duration and afterglow intensity in existing materials is solved, and a 12-hour long afterglow and 6-hour daylight excitation afterglow are achieved, with excellent flexibility and transparency.

CN119752125AActive Publication Date: 2025-04-04SUN YAT SEN UNIV

Patent Information

Application Number
CN202411904176.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The long afterglow duration and afterglow intensity of existing long afterglow polymer materials need to be further improved.

Method used

Aromatic polyester is used as the polymer matrix and tris(4-borate phenyl)amine is used as the luminescent molecule and electron donor, and the non-radiative transition process of excitons is slowed down through the formation and dissociation of the electron donor/acceptor exciton complex.

Benefits of technology

It achieves a long afterglow effect of up to 12 hours, and significantly improves the afterglow intensity under sunlight excitation, which can maintain green afterglow for up to 6 hours, while also having excellent flexibility and transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752125A_ABST
    Figure CN119752125A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of luminescent polymers, and particularly relates to a long-afterglow polymer material as well as a preparation method and application thereof. The long-afterglow polymer material is successfully prepared by taking tris (4-boric acid frequency alcohol ester phenyl) amine as a luminescence center and an electron donor and aromatic polyester with strong electron accepting capability as a polymer matrix. Wherein the tri (4-boric acid frequency alcohol ester phenyl) amine rich in electrons interacts with the aromatic polyester with strong electron-withdrawing property, so that the non-radiative transition process of excitons is effectively slowed down, and further, the long afterglow effect which can reach 12 hours at most is realized. Particularly, when the long-afterglow polymer material is excited by sunlight, the afterglow intensity is remarkably improved, green afterglow can be maintained for 6 hours, and meanwhile, the material also shows excellent flexibility and transparency. In addition, the preparation process of the material is simple and convenient, and the material is expected to be applied to the fields of flexible display, anti-counterfeiting, information storage and wearable intelligent equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent polymers, and more specifically, relates to a long afterglow polymer material and a preparation method and application thereof. Background Art

[0002] Long afterglow polymer materials, as an emerging photoluminescent material, have attracted much attention in recent years due to their unique luminescent properties. When excited by a light source, these materials can not only emit visible light, but also effectively store part of the light energy. Once the excitation light source is turned off, they can slowly release the stored energy in the form of light, thereby achieving a continuous luminescence effect ranging from seconds to hours. Long afterglow materials show great potential in many fields that require continuous lighting, such as information security, bio-imaging, and night vision systems. In addition, their ability to emit light without an external power source also makes them candidate materials in the field of energy-saving equipment.

[0003] However, long afterglow polymer materials also face a major challenge that needs to be solved: under ambient conditions, triplet excitons will undergo rapid non-radiative decay, thus affecting the persistence of luminescence. To overcome this problem, researchers have actively explored and adopted a variety of strategies to optimize the afterglow characteristics, including the introduction of heavy atoms, the design of specific molecular structures, the use of doping technology, the use of self-assembly processes, and the realization of controlled crystallization. Among them, Zhou et al. successfully obtained a polymer film with hours-long afterglow (HLA), and the afterglow time of the polymer film under ultraviolet light can last up to 11 hours. Under 5 minutes of sunlight excitation, the afterglow intensity of the film can be increased by 74 times, and this performance is currently at the forefront of known organic afterglow materials. However, although the above results have made some progress, the duration of its long-life afterglow and the afterglow intensity under sunlight excitation need to be further improved in order to achieve better results. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of existing long afterglow polymer materials, that is, the duration of long afterglow and the afterglow intensity under sunlight excitation need to be further improved, and to provide a long afterglow polymer material that can achieve a long afterglow effect of up to 12 hours and has an ultra-long life.

[0005] Another object of the present invention is to provide a method for preparing the long afterglow polymer material.

[0006] Another object of the present invention is to provide applications of the long afterglow polymer material in flexible display, anti-counterfeiting, information storage or wearable smart devices.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] The invention protects a long afterglow polymer material. The long afterglow polymer material is prepared by taking tri(4-boronic acid pinesyl ester phenyl)amine (TTB) as a fluorescent molecule and aromatic polyester as a matrix.

[0009] This application innovatively uses aromatic polyester as a polymer matrix, which not only has a strong electron-withdrawing ability, but also exhibits excellent oxygen barrier properties, thereby preventing the long afterglow from being quenched by oxygen. At the same time, tris(4-boronic acid pinesyl ester phenyl)amine, which is rich in electrons and can form a strong interaction with aromatic polyester, is selected as a fluorescent molecule and introduced into the system as a chromophore dopant and electron donor. During the excitation process, the electron donor interacts with the acceptor to form an electron donor / acceptor exciton complex, and further dissociates into anion and cation free radicals. These free radicals migrate randomly in the polymer chain, and when the free radicals carrying opposite charges recombine to form excitons (a bound state system in which electrons and holes in an insulator or semiconductor are combined by Coulomb interactions between them), an ultra-long afterglow is released. This mechanism ensures that the material can continue to emit bright and lasting afterglow after excitation.

[0010] Furthermore, the aromatic polyester includes one or more of polyethylene terephthalate (PET), polypropylene terephthalate, and polybutylene terephthalate. These substances have good electron-withdrawing ability and oxygen-barrier ability, and can form a strong interaction with tris(4-boronic acid pinesyl ester phenyl)amine.

[0011] Furthermore, the mass ratio of tris(4-boronic acid pinesyl ester phenyl)amine to aromatic polyester is 100:(0.05-3). Within this mass ratio range, the polymer material formed by mixing the two has good afterglow intensity.

[0012] Furthermore, the mass ratio of tris(4-boronic acid pinesyl ester phenyl)amine to aromatic polyester is 100:(0.08-2).

[0013] Preferably, the mass ratio of tris(4-boronic acid pinesyl ester phenyl)amine to aromatic polyester is 100:(0.1-1).

[0014] More preferably, the mass ratio of tris(4-boronic acid pinesyl ester phenyl)amine to aromatic polyester is 100:(0.4-0.6). Within this mass ratio range, the polymer material formed by mixing the two has better afterglow intensity.

[0015] The present invention protects the preparation method of the above-mentioned long afterglow polymer material, comprising the following steps:

[0016] The long afterglow polymer material is obtained by heating tri(4-boronic acid pinesyl ester phenyl)amine and aromatic polyester until they are melted and mixed evenly, and then cooling.

[0017] The preparation process of this long-afterglow polymer material is simple and cost-effective, and it is expected to be applied in flexible display, anti-counterfeiting, information storage, wearable smart devices and other fields.

[0018] Furthermore, the heating temperature is 260-280°C.

[0019] Furthermore, the heating time is 5 to 10 minutes.

[0020] Furthermore, the mixing is stirring mixing.

[0021] Furthermore, the mixing time is 1 to 3 minutes.

[0022] Furthermore, the cooling is cooling to room temperature.

[0023] The present invention protects the application of the long afterglow polymer material in the fields of flexible display, anti-counterfeiting, information storage or wearable smart devices.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present application successfully prepared a long afterglow polymer material by using tri(4-boronic acid pinnesol ester phenyl)amine as the luminescent center and electron donor, and aromatic polyester with strong electron acceptance ability as the polymer matrix. Among them, the interaction between the electron-rich tri(4-boronic acid pinnesol ester phenyl)amine and the strongly electron-withdrawing aromatic polyester effectively slows down the non-radiative transition process of the exciton, thereby achieving a long afterglow effect of up to 12 hours. In particular, when this long afterglow polymer material is excited by sunlight, the afterglow intensity is significantly improved, and the green afterglow can be maintained for up to 6 hours. At the same time, the material also shows excellent flexibility and transparency. In addition, the preparation process of this material is simple, and it is expected to be applied in the fields of flexible display, anti-counterfeiting, information storage, and wearable smart devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the afterglow spectrum of the long afterglow polymer material in Examples 1 to 3 delayed for 1 hour after being irradiated with a 365nm ultraviolet light source for 60 seconds.

[0027] Figure 2 This is a graph showing the decay curve of transient fluorescence (515 nm) of the long afterglow polymer material in Example 1 under different durations of 365 nm ultraviolet irradiation.

[0028] Figure 3This is a functional relationship diagram of the afterglow duration of the long afterglow polymer material in Example 1 and the ultraviolet irradiation duration.

[0029] Figure 4 This is a UV-visible spectrum of the long afterglow polymer material in Example 1 before and after 365nm ultraviolet irradiation.

[0030] Figure 5 This is an electron spin resonance spectrum of the long afterglow polymer material in Example 1 before and after 365nm ultraviolet irradiation.

[0031] Figure 6 This is a graph of the afterglow intensity of the long afterglow polymer material in Example 1 under different ultraviolet light source excitation wavelengths.

[0032] Figure 7 This is a two-dimensional phosphorescence spectrum of the long afterglow polymer material in Example 1 under different ultraviolet light source excitation wavelengths.

[0033] Figure 8 This is a graph showing the excitation wavelength-dependent phosphorescence spectrum of the long afterglow polymer material in Example 1.

[0034] Fig. 9 This is a fluorescence spectrum diagram of the long afterglow polymer material in Example 1 under different ultraviolet light source excitation wavelengths.

[0035] Fig.10 This is the afterglow spectrum of the long afterglow polymer material in Example 1 at different delay times.

[0036] Fig.11 This is the afterglow intensity spectrum of the long afterglow polymer material in Example 1 under 5 minutes of sunlight activation.

[0037] Fig.12 This is a graph showing the afterglow duration of the long afterglow polymer material in Example 1 under 5 minutes of sunlight activation.

[0038] Fig.13 This is a digital time statistics chart of the polymer film prepared based on the long afterglow polymer material in Example 1 after the ultraviolet irradiation is stopped. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0040] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0041] Example 1 Preparation of a long afterglow polymer material

[0042] Polyethylene terephthalate and tri(4-boronic acid pinesyl ester phenyl)amine were heated at 270° C. for 8 minutes at a mass ratio of 100:0.5 until they were molten, stirred for 2 minutes to mix the two, and cooled to room temperature to obtain a long afterglow polymer material.

[0043] Example 2 Preparation of a long afterglow polymer material

[0044] The difference from Example 1 is that the mass ratio of polyethylene terephthalate to tris(4-boronic acid pinesyl ester phenyl)amine is changed from 100:0.5 to 100:0.1.

[0045] The other steps and conditions are the same as those in Example 1.

[0046] Example 3 Preparation of a long afterglow polymer material

[0047] The difference from Example 1 is that the mass ratio of polyethylene terephthalate to tris(4-boronic acid pinesyl ester phenyl)amine is changed from 100:0.5 to 100:1.

[0048] The other steps and conditions are the same as those in Example 1.

[0049] Experimental Example 1 Physical and Chemical Properties Test of Long Afterglow Polymer Materials

[0050] 1. Determination of the effect of the mass ratio of tri(4-boronic acid pinesyl ester phenyl)amine in long afterglow polymer materials on afterglow intensity

[0051] Depend on Figure 1 It can be seen that in Examples 1 to 3, the long afterglow polymer materials showed significant differences in the change of afterglow intensity after 1 hour of irradiation with 365nm ultraviolet light. Specifically, with the initial increase in TTB content, the afterglow intensity of these materials showed an increasing trend. This phenomenon is attributed to the increase in the concentration of luminescent centers, which promotes the generation of more persistent and stable afterglow. However, when the TTB content continues to increase, the afterglow intensity begins to gradually weaken. This is because the excessively high TTB content accelerates the rate of charge recombination, resulting in a decrease in the concentration of the excited state of the luminophore, which in turn shortens the duration of the afterglow.

[0052] 2. Test the afterglow intensity and afterglow lifetime of long afterglow polymer materials under different excitation times of ultraviolet light sources.

[0053] Depend on Figures 2-3It can be seen that after the long afterglow polymer material in Example 1 is irradiated by ultraviolet light sources of different lengths (gradually increasing from 10s to 180s), the trend of the change in the afterglow lifetime and intensity shows the characteristics of first rising and then falling. Specifically, when the irradiation time is 60s, the material shows the best afterglow lifetime and intensity. This phenomenon can be attributed to the charge separation states inside the material, which are generated by ultraviolet light excitation and serve as the source of afterglow. As the ultraviolet light irradiation time increases, the concentration of charge separation states in the system gradually increases, thereby enhancing the lifetime and intensity of the afterglow. However, when the ultraviolet light irradiation time is further increased, the charge recombination rate in the system is also accelerated, resulting in a decrease in the concentration of the excited state of the luminophore, which in turn causes a slight decrease in the lifetime and intensity of the afterglow.

[0054] 3. UV-visible spectra of long afterglow polymer materials before and after excitation by UV light source

[0055] After being irradiated by ultraviolet light, the long afterglow polymer material in Example 1 has the following spectral characteristics: Figure 4 As shown, there are two obvious absorption peaks, located at 582nm and 701nm respectively. These two absorption peaks correspond to the characteristic absorption of PET anion radicals and TTB cation radicals respectively. This result strongly proves that under the excitation of ultraviolet light, the charge separation process of electron donor and acceptor successfully occurs between the fluorescent molecule and the aromatic polyester, thereby generating anion radicals and cation radicals.

[0056] 4. Determination of the change of electron spin resonance (ESR) signal of long afterglow polymer materials before and after excitation by ultraviolet light source

[0057] In Example 1, after the long afterglow polymer material was irradiated with 365nm ultraviolet light, the ESR test was performed using a JEOL JES-FA200 instrument. The test results are as follows: Figure 5 As shown in the figure, a significant ESR signal is clearly shown, which indicates that free radicals are generated during the irradiation process. This result further confirms the generation of PET anion radicals and TTB cation radicals.

[0058] 5. Determination of the intensity / phosphorescence (RTP) / fluorescence (FL) spectra of hourly level afterglow (HLA) of long afterglow polymer materials at different excitation wavelengths

[0059] First, after being irradiated by excitation light of different wavelengths, the long afterglow polymer material in Example 1 is Figure 6It can be seen that in the wavelength range of 350-390nm, the intensity of HLA gradually increases with the increase of excitation wavelength; while in the range of 390-440nm, the intensity of HLA gradually weakens with the increase of excitation wavelength. This phenomenon shows that the HLA of long afterglow polymer material has the property of excitation wavelength response, and it can be effectively excited in the wide wavelength range of 350-440nm, indicating that it can also be excited by visible light in a certain wavelength range (visible light wavelength range: 390-780nm) to produce afterglow.

[0060] Secondly, after being irradiated by ultraviolet light sources of different wavelengths, the long afterglow polymer material in Example 1 is Figure 7 It can be seen that, similar to the observation of HLA intensity, in the range of 350-400nm excitation wavelength (Ex. Wavelength), the intensity of RTP gradually increases with the increase of excitation wavelength; while in the range of 400-500nm, the intensity of RTP gradually weakens with the increase of excitation wavelength. It can be seen that the RTP behavior of this material also depends on the excitation wavelength, which covers a range of 350-500nm. It is worth noting that the emission spectrum of RTP shows a significant red shift phenomenon with the increase of excitation wavelength ( Figure 8 ), which is attributed to the aggregation of chromophore molecules.

[0061] Finally, after being irradiated by excitation light sources of different wavelengths, the long afterglow polymer material in Example 1 is Fig. 9 It can be seen that its maximum emission wavelength remains relatively stable, but the FL intensity changes significantly with the change of excitation wavelength. When comparing FL with RTP, it can be clearly seen that RTP shows a higher sensitivity to the excitation wavelength, and both its intensity and maximum emission wavelength are affected, while the change of FL intensity is more significant. This difference stems from the different excited states generated by these two emissions.

[0062] From the above, it can be concluded that the long afterglow polymer material can simultaneously emit three types of light, namely long afterglow, fluorescence and phosphorescence, when excited by an ultraviolet light source, which fully demonstrates its potential to adapt to different application requirements.

[0063] 6. The duration of afterglow of long afterglow polymer materials after being excited by ultraviolet light source

[0064] Depend on Fig.10 It can be seen that the long afterglow polymer material in Example 1 has a gradually weakened afterglow intensity over time within 1 to 12 hours after the UV light source stops irradiating. It is worth noting that even after 12 hours of stopping the UV light source, an afterglow signal significantly higher than the background value (bg) can still be detected at a wavelength of 515nm, which fully proves that after the UV light stops irradiating, the long afterglow polymer material has a long afterglow characteristic of up to 12 hours.

[0065] 7. Afterglow intensity and duration of long afterglow polymer materials after sunlight excitation

[0066] Depend on Fig.11 It can be seen that by exposing the long afterglow polymer material in Example 1 to sunlight for 5 minutes, the afterglow intensity can be significantly enhanced, and the green afterglow produced is clearly visible to the naked eye. Compared with the intensity before irradiation, the afterglow intensity has been increased by up to 1257 times. In addition, when the sunlight stops irradiating, the afterglow intensity gradually weakens over time within 0.25 to 6 hours, but after 6 hours of stopping the irradiation, the afterglow signal can still be detected at a wavelength of 530nm, which fully proves that after the sunlight stops irradiating, the afterglow of the long afterglow polymer material can last up to 6 hours ( Fig.12 ).

[0067] Experimental Example 2: Flexible display test of polymer film prepared based on long afterglow polymer material

[0068] 1. Experimental Methods

[0069] The PET powder was heated to 270°C until it was completely melted. Then, the fluorescent molecules were quickly added and stirred thoroughly to ensure a uniform mixture. The mixture was then pressed into a polymer film with a thickness of 1 mm.

[0070] 2. Experimental results

[0071] Depend on Fig.13 It can be seen that when the polymer film is irradiated with an ultraviolet light source with a wavelength of 365nm for 1 minute, the film immediately emits nanosecond blue fluorescence corresponding to the preset pattern. Once the ultraviolet irradiation is stopped, the blue light fluorescence is rapidly quenched, and then turns into green phosphorescence at the millisecond to second level, and exhibits a long afterglow effect. Subsequently, in the next 0 to 100 seconds, the bright green afterglow is clearly visible. In the time period of 100 to 3600 seconds, although the intensity of the afterglow gradually decreases, it still remains relatively bright. This polymer afterglow system, which can continue to emit light for several hours with only 1 minute of excitation, has potential application value in the field of efficient flexible display; in addition, the above-mentioned long afterglow polymer material has unique luminescence properties, excellent long afterglow effect, and excellent flexibility and transparency, making it also suitable for anti-counterfeiting, information storage and wearable smart devices.

[0072] In summary, the present application successfully prepared a long afterglow polymer material by using a clever molecular doping strategy, using tri(4-boric acid pinesol ester phenyl)amine as a luminescent center and electron donor, and an aromatic polyester with strong electron-accepting ability as a polymer matrix. In this material, the electron-rich tri(4-boric acid pinesol ester phenyl)amine interacts with the strongly electron-withdrawing aromatic polyester, effectively slowing down the non-radiative transition process of the exciton. Therefore, the long afterglow polymer material prepared under the optimal preparation conditions exhibits a long afterglow effect of up to 12 hours under ultraviolet light. In particular, when this long afterglow polymer material is excited by sunlight, the afterglow intensity is significantly improved, and the green afterglow can be maintained for up to 6 hours, and the material also exhibits excellent flexibility and transparency.

[0073] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A long afterglow polymer material, characterized in that: The long afterglow polymer material is prepared by using tri(4-boronic acid pinesyl ester phenyl)amine as a fluorescent molecule and aromatic polyester as a matrix.

2. The long afterglow polymer material according to claim 1, characterized in that: The aromatic polyester includes one or more of polyethylene terephthalate, polytrimethylene terephthalate, and polybutylene terephthalate.

3. The long afterglow polymer material according to claim 1, characterized in that: The mass ratio of the tris(4-boronic acid pinesyl ester phenyl)amine to the aromatic polyester is 100:(0.05-3).

4. The long afterglow polymer material according to claim 3, characterized in that: The mass ratio of the tris(4-boronic acid pinesyl ester phenyl)amine to the aromatic polyester is 100:(0.08-2).

5. The long afterglow polymer material according to claim 4, characterized in that: The mass ratio of the tris(4-boronic acid pinesyl ester phenyl)amine to the aromatic polyester is 100:(0.1-1).

6. The long afterglow polymer material according to claim 5, characterized in that: The mass ratio of the tris(4-boronic acid pinesyl ester phenyl)amine to the aromatic polyester is 100:(0.4-0.6).

7. The method for preparing the long afterglow polymer material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The long afterglow polymer material is obtained by heating tri(4-boronic acid pinesyl ester phenyl)amine and aromatic polyester until they are melted and mixed evenly, and then cooling.

8. The preparation method according to claim 7, characterized in that: The heating temperature is 260-280°C.

9. The preparation method according to claim 7, characterized in that: The heating time is 5 to 10 minutes.

10. Application of the long afterglow polymer material according to any one of claims 1 to 6 in the fields of flexible display, anti-counterfeiting, information storage or wearable smart devices.

Citation Information

Patent Citations

  • Compound with D-pi-A structure as well as preparation method and application of compound

    CN116283723A

  • Long-afterglow material as well as preparation method and application thereof

    CN117004383A

  • Colored light-cured long-afterglow ink as well as preparation method and application thereof

    CN118599523A

  • Long Persistent Luminescence Emitter and Long Persistent Luminescent Element

    US20180346807A1

Cited By

  • Polymer with thermally enhanced long afterglow characteristic as well as preparation method and application thereof

    CN120329693A

  • Long afterglow material based on waste PET as well as preparation method and application of long afterglow material

    CN121045753A